Best Answer

If for x = -1 we find the same value of y in both equations, then x = -1 will be a part of the solution of the system.

Let's suppose that x = -1 is the x-coordinate of the solution of the given system

x + y = 4

x - y = 6.

x + y = 4

-1 + y = 4

-1 + 1 + y = 4 + 1

y = 5

x - y = 6

-1 - y = 6

-1 - 6 + y - y = 6 - 6 + y

-7 = y

Since we have two different values for y, we say that x = -1 is not a part of the solution for the given system.

Q: Is x equals -1 is a solution of x plus y equals 4 x-y equals 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x+xy=8 xy=-x+8 y=-1+8/x

The solution is (x, y, z) = (2.5, 1, 2.5).

solution: y = 0 x = -1

Not sure what you mean; that equation certainly has a solution.

xy + x + y + 1 is an expression, not an equation. An expression cannot be solved.

Related questions

It equals y+1

x+xy=8 xy=-x+8 y=-1+8/x

The solution is: x = 1 and y = -1

xy + x + y + 1 = (x + 1)(y + 1).

That is the commutative property of equality.

xy = x ÷x y = 1

No.

In the equations Y=X-1 and Y=-X+1, the solution is (1,0)

It is (-1, 3).

1 solution

The solution is (x, y, z) = (2.5, 1, 2.5).

solution: y = 0 x = -1